If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4y + 6 = -2(3y + 2) Reorder the terms: 6 + -4y = -2(3y + 2) Reorder the terms: 6 + -4y = -2(2 + 3y) 6 + -4y = (2 * -2 + 3y * -2) 6 + -4y = (-4 + -6y) Solving 6 + -4y = -4 + -6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6y' to each side of the equation. 6 + -4y + 6y = -4 + -6y + 6y Combine like terms: -4y + 6y = 2y 6 + 2y = -4 + -6y + 6y Combine like terms: -6y + 6y = 0 6 + 2y = -4 + 0 6 + 2y = -4 Add '-6' to each side of the equation. 6 + -6 + 2y = -4 + -6 Combine like terms: 6 + -6 = 0 0 + 2y = -4 + -6 2y = -4 + -6 Combine like terms: -4 + -6 = -10 2y = -10 Divide each side by '2'. y = -5 Simplifying y = -5
| (x+21)=(2x-14) | | 2(4n+9)=-6+8(3-12n) | | 25u^6v^6y-10u^7v^7= | | 16Y-8(3y-2)=24 | | 6x-9=12+3x | | 5(r-7)=8(r+2) | | 2(4x+4)=10x+6-2x+2 | | 3n-17=3+5n | | 4-5w=-2w | | -7Y+4=60 | | 25x=625 | | -3+4(1-3m)=-12(m-11) | | 16m^2-8m-3= | | y=3x^2+12x+7 | | X+10Y=47 | | ln(2x+3)=ln(2x-1) | | -7(v-5)=-7(v+8) | | 16=16H | | 2x^2-8x-80=0 | | 8t-18=38+t | | X+6+6x=41 | | -7(v-5)=-7 | | 100x^2-y^4= | | 20s+4=13c-10 | | 9(x+6)=-9(3+2x) | | 7m-15-10m=6 | | (3y+5)=(4y-10) | | 5x^2=2+3x | | 5w+6-w=2 | | 4x+6=2x^2 | | 5x^2+2=3x | | 0=9x^2-39x+24 |